Asymmetric total syntheses of (+)- and (-)-spirotryprostatins A and B - Sebahar, Paul Richard, author; Williams, Robert M., advisor (Colorado State University. Libraries, 2003)
The first published total synthesis of (+)- and (-)-spirotryprostatin B is presented. The synthesis features an asymmetric azomethine ylide [1,3]-dipolar cycloaddition reaction. Additionally, a Barton-modified Hunsdiecker reaction was demonstrated as means of affecting an oxidative decarboxylation. Intermediates along the synthesis were studied for their biological activity as G2/M phase cell cycle inhibitors and microtubule assembly inhibitors. The asymmetric azomethine ylide [1,3]-dipolar cycloaddition was also studied in greater detail. Varying the aldehyde component of the reaction resulted in the formation three different cycloadducts. Theoretical calculations for the reaction were compared with observed results. Attempts to synthesize (-)-spirotryprostatin A are also presented. Two different strategies based on the synthesis of (+)- and (-)-spirotryprostatin B were explored.
Keywords: Asymmetric synthesis